Konsep Fintech Lending Dalam Perspektif Maqāṣid Syarī’ah - Mochamad Novi Rifa’i Rifa’i (Faculty of Economics and Management, 2020)
The development of technology is an inevitability faced by the financial business world. The existence of technology should be able to assist people in their activities, including in financing and financial management activities, instead of becoming a trap of debt accumulation. The existence of fintech lending has simplified the process of financial transactions in a fast process via smartphone.In this study, researchers want to know the concept of maqasid shariah looking at existing fintech lending. This qualitative study used a phenomenological approach which discusses the existence of fintech lending in the perspective of the maqasid shariah. Additionally, this research obtained both primary and secondary data from websites, survey reports and research papers. The result showed that the basis of financial cooperation is mubah (permissible), it should be noted that the concept of fintech lending must be in line with the perspective of the maqasid shariah, which is preventing the badness, obtaining the optimum benefits and preventing from mudhārāt. Based on the maqasid shariah, the application of fintech lending should fit at least six requirements as follows; first,a transparent contract model agreement before the transaction, which encloses the rights and responsibilities of both parties. Additionally, the cooperation should be in line with the shariah. Second, the operator must use AI (Artificial Intelligence),and the user of capital must pass AI. Third, if the lending model is a business collaboration, then the risk of failure will require a detailed explanation. When the failure is due to force majeure, so both parties should cover the loss, and when it failure appears due to the miss management, then the user will be responsible for it. Fourth, if the lending model is a qard contract, the manager must be ready if the manager has not been able to return or not the qarḍ. Fifth, the problems that occur must be resolved in a dignified manner without degrading all parties. Sixth, the provider of funds or operators must be able to maintain the data confidentiality offunds users. Seventh, all forms of funds given must be used under their purpose and may not carry out activities against the Shariah.